Electrical circuits [ Ohm's law (Electricity and electronics, 2006)
"This video uses 3-D animation and live action to make basic electrical circuits come to life. The properties of series, parallel, and series-parallel circuits are easy to grasp when you can see the electrons flow through each circuit leg in each circuit type. Ohm's Law is illustrated with animated pie charts and basic calculations that isolate each section of the circuit."--Container